RETRACTED: A Systematic Review of Barriers in Adoption of Environmental Management Accounting in Chinese SMEs for Sustainable Performance - Javed, Fahad; Yusheng, Kong; Iqbal, Najaf; Fareed, Zeeshan; Shahzad, Farrukh (Frontiers in Public Health, 2022)
Small and medium sized enterprises (SMEs) play an important role in sustainable development not only for their significant contribution to China’s economy but also for their large share of total discharged pollutants. Despite the widely acknowledged importance and benefits of Environmental Management Accounting (EMA), the level of adoption and implementation of EMA practice is still weak within SMEs in many countries, especially in China. The current systematic review aims to identify the barriers affecting the Chinese SMEs for adopting environmental management accounting practices along with the critical success factors required for adopting EMA practices by SMEs and their top management for ensuring sustainable corporate environmental performance in China. The study is carried out following the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA) guidelines. Seventy-three articles were found to be eligible to be included in the systematic review, which was published on EMA in small and medium-sized enterprises in China. Our study aims to document barriers to the adoption of EMA among Chinese SMEs. The review concluded that strict legislation and the availability of flexible financing options for SMEs can promote the adoption of EMA by SMEs. The establishment of environmental reporting systems and auditing mechanisms can further increase the utilization of EMA by small and medium firms. Barriers to EMA adoption can be mitigated after careful consideration of the current situation in SMEs. Documentation of significant barriers may help to form supportive policies which ultimately add to the efforts towards climate change mitigation.